Mennesket som Mikrokosmos. Grundtvigs digt om »Menneske-Livet« - Gregersen, Niels Henrik (Grundtvig-Studier, 2000)
The Human Being as a Microcosm: Grundtvig's Great Poem on Human Life’ By Niels Henrik Gregersen All of Grundtvig’s hymns are about human existence but only one hymn is actually entitled ‘Human Life’ (Sang- Værk IV, 173). This long poem from 1847, widely neglected in Grundtvig scholarship, describes the human potential for growth and transformation, and does so with a consistent use of five symbols of nature: Nature as star, rock, ocean, bird and flower. Through the lens of these five natural symbols (all of which have strong Biblical allusions) Grundtvig describes seven steps of human self-transformation in the image and likeness of God. The egotistic human heart is, first, likened to the coldness of the heavenly stars. In a second step, the superiority of humanity over nature is described in terms of the human capacity to discern life’s meaning (the eye is greater than the star) and to express it in terms of language (the word is even greater than the eye). In a third step, the human being is described as comprising nature in its fullness (the star is in the eye as well as behind the brow). In a fourth step, the human being is described in its painful lack of eternity, despite its fullness compared with other created beings. In a fifth step, a Christology of longing is presented, according to which Christ comprises what the human being does not comprise: time and eternity in one person. Thus, the high star of Bethlehem leads the human mind to the low crib of the poor child, in whom nature and spirit, time and eternity were united; by contrast, human existence is temporal but is longing for eternity. In a sixth step, humanity is transformed into the image and likeness of Jesus Christ. This process finally leads, in the seventh step, to a new song, a praising of God which takes up and yet renews Psalm 8 of the Old Testament. It is argued that Grundtvig understands the human being after the model of Christ. The notion of imago dei is portrayed in similitudine Christi. According to Col 1,15 f, Christ comprises both the heavens and earth, both the visible and the invisible realms of reality. Just as Jesus Christ was God and man in one person (»distinctively, yet not separated« as it was said in the Chalcedonian formula of 431), so does the human being comprise both the natural and spiritual realm of reality. Christ is the archetypical microcosm, humanity is the ectypical microcosm who, ideally at least, combines nature and spirit. On this interpretation, Grundtvig is seen as a Christian Platonist, who consistently uses the ‘principle of plenitude’ (Arthur Lovej oy), but combines it with a strong emphasis on the human being as a microcosm of both the physical and the spiritual realms of reality. This Platonic-Christian notion of humanity as ‘double microcosm’ explains why Grundtvig, in one and the same poem, can describe human existence as being nature in its fulness, and yet as superior to nature. It also explains his critical stance vis-a-vis the Romantic philosophy of nature. Also Grundtvig’s nephew, the philosopher Heinrich Steffens, used the idea of humanity as a microcosm in his famous Prolegomena to Philosophical Lectures from 1803. But unlike Steffens, Grundtvig refuses to speak of a gradual transformation from nature to the emergence of the spirit. In Grundtvig’s view, there is no slide from nature to spirit; rather, the spiritual realm is prior to the realm of physical nature. Against this background, Grundtvig could only understand the Romantic vision of humanity as the spirit of nature as a bisected version of the full Christian idea of the human being as a microcosm. On this important point, Grundtvig departed from his fellow-Romanticists.